Phytobezoars in the Stomach and Small Bowel: CT Findings - Sun, Zhonghua; Al-Naami, A.; Ali Athlawy, A.; Ali Khan, L. (Bentham Science Publishers, 2014)
Phytobezoars in the small bowel are rare and most frequently demonstrate obstructive effects leading to small bowel obstruction. Several case reports on the radiological findings of primary small bowel phytobezoars are available in the literature. However, very little is published on the CT findings. We present the CT results in a patient with phytobezoars in the stomach and small bowel with secondary small bowel obstruction, and highlight the diagnostic value of CT imaging.